Educational Research: The Importance and Effects of Institutional Spaces - Smeyers, Paul.; Depaepe, Marc.; Keiner, Edwin. (Educational Research ;, 2013)
This collection of fresh analyses aims to map the links between educational theory and research, and the geographical and physical spaces in which teaching is practiced and discussed. The authors combine historical and philosophical perspectives in examining the differing institutional loci of education research, and also assess the potential and the limitations of each. The contributors trace the effects of space on educational practice in the classroom, in the broader institutions, and in the academic discipline of educationdoing so for a range of international contexts. The chapters address various topics relating to the physical and geographical environment. How, for example, does geographical space shape researchers mental frameworks? How did the learning environments in which young children are taught today evolve? To what extent did parochialism shape Americas higher education system? How can our understanding of classroom practice be enhanced by concepts of space? The book acknowledges that texts themselves, as well as the research arena, are spaces too, and notes the fascinating debate on the concept of space in the field of mathematics education. Indeed, as more and more students move online, the book analyses the rising importance of virtual spaces such as Web 2.0, which have major educational implications for researchers and students joining the innovative virtual universities of the future. This publication, as well as the ones that are mentioned in the preliminary pages of this work, were realized by the Research Community (FWO Vlaanderen / Research Foundation Flanders, Belgium) Philosophy and History of the Discipline of Education: Faces and Spaces of Educational Research.